Optical Signatures of Defect Centers in Transition Metal Dichalcogenide Monolayers. Issue 3 (3rd February 2021) - M. C. de Melo, Pedro Miguel; Zanolli, Zeila; Verstraete, Matthieu J.
Abstract: Even the best quality 2D materials have non‐negligible concentrations of vacancies and impurities. It is critical to understand and quantify how defects change intrinsic properties, and use this knowledge to generate functionality. This challenge can be addressed by employing many‐body perturbation theory to obtain the optical absorption spectra of defected transition metal dichalcogenides. Herein metal vacancies, which are largely unreported, show a larger set of polarized excitons than chalcogenide vacancies, introducing localized excitons in the sub‐optical‐gap region, whose wave functions and spectra make them good candidates as quantum emitters. Despite the strong interaction with substitutional defects, the spin texture and pristine exciton energies are preserved, enabling grafting and patterning in optical detectors, as the full optical‐gap region remains available. A redistribution of excitonic weight between the A and B excitons is visible in both cases and may allow the quantification of the defect concentration. This work establishes excitonic signatures to characterize defects in 2D materials and highlights vacancies as qubit candidates for quantum computing. Abstract : Large and pristine monolayers of transition metal dichalcogenides are difficult to manufacture, with most of them containing defects. Herein it is shown, using many‐body perturbation theory, how different vacancies and substitutions can be spectrally identified in monolayer WS2 and might increase its functional potential, creating new quantum dots or adsorption sites.